Pervasive glycative stress links metabolic imbalance and muscle atrophy in early-onset Parkinson's disease - Natalia Prudente de Mello; Michelle Tamara Berger; Kim A. Lagerborg; Yingfei Yan; Jennifer Wettmarshausen; Susanne Keipert; Leopold Weidner; Janina Tokarz; Gabriele Möller; Stefano Ciciliot; Safal Walia; Yiming Cheng; et al. (Molecular Metabolism)
Objective: Parkinson’s disease (PD) is recognized as a systemic condition, with clinical features potentially modifiable by dietary intervention. Diets high in saturated fats and refined sugars significantly increase PD risk and exacerbate motor and non-motor symptoms, yet precise metabolic mechanisms are unclear. Our objective here was to investigate the interplay between diet and PD-associated phenotypes from a metabolic perspective. Methods: We explored PARK7 KO mice under chronic glycative stress induced by prolonged high-fat high-sucrose (HFHS) diet. We investigated metabolic consequences by combining classical metabolic phenotyping (body composition, glucose tolerance, indirect calorimetry, functional assays of isolated mitochondria) with metabolomics profiling of biospecimens from mice and PD patients. Results: We found this obesogenic diet drives loss of fat and muscle mass in early-onset PD mice, with a selective vulnerability of glycolytic myofibers. We show that PD mice and early-onset familial PD patients are under pervasive glycative stress with pathological accumulation of advanced glycation end products (AGEs), including N-α-glycerinylarginine (α-GR) and N-α-glycerinyllysine (α-GK), two previously unknown glycerinyl-AGE markers. Conclusions: Our results offer the first proof for a direct link between diet, accumulation of AGEs and genetics of PD. We also expand the repertoire of clinically-relevant glycative stress biomarkers to potentially define at-risk patients before neurological or metabolic symptoms arise, and/or to monitor disease onset, progression, and effects of interventions.